And wrote my story anyway : black South African women's novels as feminism - Boswell, Barbara ([Place of publication not identified] : Wits University Press, 2021)
Part literary history, part feminist historiography, Barbara Boswell's And Wrote My Story Anyway: Black South African Women's Novels as Feminism examines ten novels and places them in a conversation with each other. The result is an arc of feminist criticism speaking forcefully to racist, white-dominated, patriarchal power.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 9, 2020).
eBooks on EBSCOhost
Keywords: Women, Black -- South Africa; Feminists -- South Africa; Racism -- South Africa; Feminist criticism -- South Africa; Nationalism -- South Africa; Women in literature; Feminist literary criticism -- South Africa; Femmes noires -- Afrique du Sud; Féministes -- Afrique du Sud; Racisme -- Afrique du Sud; Critique féministe -- Afrique du Sud; Nationalisme -- Afrique du Sud; Femmes dans la littérature.; Feminist criticism; Feminists; Nationalism; Racism; Women, Black; Women in literature; South Africa